2014
DOI: 10.1159/000362457
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Induces Epithelial-Mesenchymal Transition through Autophagy via Activation of c-Src Kinase

Abstract: Background: Endoplasmic reticulum (ER) stress has been implicated in inducing epithelial-mesenchymal transition (EMT). ER stress is also known to induce autophagy. However, it is unclear whether ER stress-induced autophagy contributes to EMT. We hypothesized that ER stress might induce EMT through autophagy via activation of c-Src kinase in tubular epithelial cells. Method: All experiments were performed using HK-2 cells. Protein expression was measured by Western blot analysis. Immunofluorescence and small in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 55 publications
3
39
0
Order By: Relevance
“…ER stress is also a known cause of EMT and we previously reported that ER stress was able to induce EMT in renal tubular cells [34]. In this study, we found that losartan could suppress the tunicamycin-induced EMT as well.…”
Section: Discussionsupporting
confidence: 59%
“…ER stress is also a known cause of EMT and we previously reported that ER stress was able to induce EMT in renal tubular cells [34]. In this study, we found that losartan could suppress the tunicamycin-induced EMT as well.…”
Section: Discussionsupporting
confidence: 59%
“…EMT is a process that alveolar epithelial cells (AECs) are transformed into the phenotype of mesenchymal cells such as myofibroblasts. During EMT, AECs lose the specific epithelial markers, such as zonula occludens-1 (ZO-1), E-cadherin and cytokeratin, and gain mesenchymal markers, such as vimentin, ␣-smooth muscle actin (␣-SMA), and fibroblast specific protein 1 (FSP-1) (Moon et al, 2014). Previous researches suggest that endoplasmic reticulum (ER) stress plays an incredible role in EMT in the progression of lung fibrosis (Tanjore et al, 2015;Zhao et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of previous studies focused on its reverse signalling, ie, that ER stress induces EMT and autophagy (33); in contrast, a recent report revealed that EMT can sensitize cells to ER stress by activating the PERK-elF2α axis of the UPR (12). In our present study, this sensitization seems to be due to the loss of the endogenous ER stress response/UPR signalling although it remains unclear how the loss of/altered USF3 could lead to the loss of ER stress response/UPR.…”
Section: Discussionmentioning
confidence: 99%